SIMULATION OF TRANSPORT POLICY ALTERNATIVES FOR COLOMBIA - Roberts, P O; Kresge, D T (American Economic Review, 1968)
A MACROECONOMIC AND TRANSPORT MODEL HAS BEEN DEVELOPED TO EXPLORE THE INTERFACE BETWEEN THE ECONOMY OF AN UNDERDEVELOPED NATION AND ITS TRANSPORTATION SYSTEM. THE MACROECONOMIC PORTION OF THE MODEL PRODUCES ANNUAL PROJECTIONS OF REGIONAL DEMANDS, PRODUCTION LEVELS, AND INCOMES. THE TRANSPORT SECTOR DETERMINES MARKET AREAS, DISTRIBUTION AND ROUTING OF THESE COMMODITY FLOWS, AND ASSIGNS THEM TO THE LINKS OF A NETWORK REPRESENTING THE INDIVIDUAL TRANSPORT FACILITIES EXISTING OR PROPOSED FOR THE COUNTRY OR REGION UNDER STUDY. THE COUNTRY OF COLOMBIA, SOUTH AMERICA WAS CHOSEN FOR EXPERIMENTATION WITH THE MODEL. IT IS CONCLUDED THAT THE MODEL IS USEFUL FROM BOTH A PRACTICAL AND A PEDAGOGICAL STANDPOINT. IN THE DISCUSSION, IT IS NOTED THAT THE CRUX OF THE MATTER MAY WELL BE IN THE DYNAMIC INTERACTION BETWEEN THE TRANSPORTATION SECTOR AND THE REST OF THE ECONOMY. A PRINCIPAL FEATURE OF THIS MODEL IS JUST THIS DYNAMIC INTERACTION. IT IS CONCLUDED THAT THE ABOVE MODEL CANNOT HELP WITH SOME IMPORTANT CLASSES OF TRANSPORT QUESTIONS, BUT THAT THERE ARE A LARGE NUMBER OF TRANSPORT PROBLEMS IN LESS DEVELOPED ECONOMIES FOR WHICH IT IS WELL SUITED. /BPR/